Fundamentals of chemical reaction engineering - Davis, Mark E. (McGraw-Hill, 2003)
This book introduces the quantitative treatment of chemical reaction engineering. The text provides a balanced approach: first, it covers both homogeneous and heterogeneous reacting systems; second, it covers both chemical reaction engineering and chemical reactor engineering